Enhanced Yield of Green Corn Through Biofertilizer and Foliar Fertilizer Application in Double-Row Corn Planting Technology - Datul, Emmanuel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to evaluate the performance of white corn (green corn) under double-row planting combined with biofertilizer and foliar fertilizer applications to improve growth, yield, and economic viability. Grounded in principles of sustainable agriculture and integrated crop management, the study employed a randomized complete block design with six treatment combinations replicated four times under field conditions representative of corn-growing areas in Isabela. Data were collected through standard field measurements and soil analysis, including plant height, ear characteristics, biomass, and yield, and analyzed using Analysis of Variance (ANOVA). Results showed that plant height across growth stages did not differ significantly among treatments, indicating limited influence of fertilization strategies on vegetative growth. However, significant improvements were observed in reproductive traits, biomass, and yield. The treatment combining recommended fertilizer rate with biofertilizer and foliar fertilizer consistently produced superior results, while the use of biofertilizer and foliar fertilizer alone resulted in the lowest performance. Pest and disease pressures, including fall armyworm and eyespot disease, affected crop performance and highlighted the need for integrated pest management. The study concludes that integrated nutrient management combined with double-row planting enhances white corn productivity, with biofertilizers and foliar fertilizers serving as effective supplements but not substitutes for soil-based fertilization. It is recommended that farmers adopt integrated fertilization strategies and strengthen pest management practices to improve yield and sustainability. The study supports SDG 2 (Zero Hunger), SDG 8 (Decent Work and Economic Growth), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action) by promoting efficient, sustainable, and climate-resilient agricultural practices. Its sustainability impact lies in improving soil health, increasing farmer income, and supporting environmentally responsible corn production systems.
Keywords: Biofertilizer; Double-row planting; Foliar fertilizer; Green corn; Integrated nutrient management; Sustainable agriculture; White corn; Yield performance